The Impact of Façade Orientation and Woody Vegetation on Summertime Heat Stress Patterns in a Central European Square: Comparison of Radiation Measurements and Simulations - Noémi Kántor; Csilla Viktória Gál; Ágnes Gulyás; János Unger (Advances in Meteorology)
Increasing summertime air temperature deteriorates human health especially in cities where the warming tendency is exacerbated by urban heat island. Human-biometeorological studies shed light on the primary role of radiation conditions in the development of summertime heat stress. However, only a limited number of field investigations have been conducted up to now. Based on a 26-hour long complex radiation measurement, this study presents the evolved differences within a medium-sized rectangular square in Szeged, Hungary. Besides assessing the impact of woody vegetation and façade orientation on the radiation heat load, different modeling software programs (ENVI-met, SOLWEIG, and RayMan) are evaluated in reproducing mean radiant temperature (Tmrt). Although daytime Tmrt can reach an extreme level at exposed locations (65–75°C), mature shade trees can reduce it to 30–35°C. Nevertheless, shading from buildings adjacent to sidewalks plays also an important role in mitigating pedestrian heat stress. Sidewalks facing SE, S, and SW do not benefit from the shading effect of buildings; therefore, shading them by trees or artificial shading devices is of high importance. The measurement–model comparison revealed smaller or larger discrepancies that raise awareness of the careful adaptation of any modeling software and of the relevance of fine-resolution field measurements.